Status dan Peralihan Hak atas Saham Perseroan Terbatas Milik Pemegang Saham yang Meninggal Dunia - Karissa, Nadhila Rianda; Lumbang Tobing, David Maruhum (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In a condition where a shareholder of a Limited Liability Company (PT) dies, a problem arises as to the status of ownership of the rights. This study analyzes how the status of ownership of rights if the shareholders have died, especially regarding rights as a shareholder and the procedure for transfer of shares due to inheritance to their heirs, shall be stated in the deed of transfer of shares first. This research method is juridical normative which is done by researching library materials or secondary data. The results of this study indicate that the share ownership status of the deceased shareholder, if it has not been transferred in accordance with the procedures regulated by the Company Law, the shareholder's rights have not been transferred to his heirs, so to take legal action against the share the heirs must make a deed of transfer of shares due to the inheritance that occurs, followed by the recording of the name of the heir in the PT’s Registry Shareholders. Suggestions for this research are the need for socialization from PT and Notary regarding the procedure for transfer of shares and the need for making implementing regulations from the Company Law which further regulates the transfer of shares due to inheritance